Financial Inclusion and the Trade-Growth Nexus: Evidence from the Emerging Zimbabwean Economy - Maune, Alexander (Journal of Economics and Behavioral Studies, 2019)
This study examined the effect of financial inclusion in the trade-growth nexus in Zimbabwe using time series data collected from the World Bank databases from 1980 to 2016. The study precisely examined whether financial inclusion is a passage within which trade openness impacts growth in Zimbabwe. Also examined was the complementarity effect of financial inclusion and trade openness on growth. The effect of financial inclusion and trade openness on growth has received much attention from researchers across the globe and literature is awash with theoretical and empirical evidence of such studies. What is yet to be examined is whether financial inclusion is a passage within which trade openness influences growth. The study finds a negative significant effect of financial inclusion and trade openness on growth in Zimbabwe. Moreover, the findings show a complementary, strong and positive nexus linking financial inclusion and trade openness on growth in Zimbabwe. Policy-makers are, however, implored to formulate policies meant to deepen financial inclusion in order to enhance growth through trade openness. The article will help expand the academic knowledge and as such contribute in filling the gap that exists within the body of knowledge. The article is important to policy-makers, the academia, private sector and researchers at large.